Étudier les représentations des paysages sur les réseaux sociaux - Aurélien Allouche (Projets de Paysage)
This article examines representations of landscapes disseminated by online image sharing sites. It proposes an original methodology based on the analysis of similarities used in social psychology. By applying this methodology in the case of Camargue, the author demonstrates that the digital representations of landscapes can reconnect with local cultural roots, in spite of the fact that by nature they are disconnected from the territory. He also describes the role played by certain natural environments in associations of heterogeneous social representations.